Effect of the 2D-LoA instructional model on vocational students' learning outcomes in higher education - Wakid, Muhkamad; Sofyan, Herminarto; Gunadi, Gunadi; Ilma, Arina Zaida (Edelweiss Applied Science and Technology, 2025)
This study aims to help vocational students in higher education learning environments. One way to achieve this goal is by using the 2D-LoA instructional model. This model is based on the widening gap between theoretical and practical knowledge, especially technical skills for vocational students. This quasi-experimental study compared the learning outcomes of 34 automotive engineering students following pre-test and post-test assessments. The experimental group was given treatment with the 2D-LoA model, while the control group received traditional learning. The independent samples t-test analysis showed that the experimental group significantly improved practical learning outcomes (p < 0.05) and demonstrated an average N-gain on practical skills of 0.58. However, practical learning outcomes did not show improvement as predicted by previous learning outcome models but indicated a positive trend (p=0.08). These findings contribute to practical skills, an essential aspect of vocational education, using the 2D-LoA model. The study emphasizes the promise of the 2D-LoA instructional approach in providing non-immersive computer-based interactivity for learners, as opposed to the passive absorption of theoretical concepts. More moderate results in enhancing the learning of theoretical concepts point to a need to improve the model to better aid the learning of concepts. The practical implications of this study are that teachers can use the 2D-LoA model in subjects that require a strong mastery of practical skills, such as science, technology, and vocational education.